2020
DOI: 10.1177/1558944720911213
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Psychosocial Factors as Predictors of Pain Relief Following Nerve Surgery

Abstract: Background: Peripheral nerve injuries may result in pain, disability, and decreased quality of life (QoL). Pain is an incompletely understood experience and is associated with emotional and behavioral qualities. We hypothesized that pain following peripheral nerve surgery could be predicted by changes in emotions or QoL postoperatively. Methods: Using prospectively collected data, a retrospective study design was used to evaluate the relationships among pain, QoL, and psychosocial factors in patients who under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…The ZCMEI-21 has been previously validated in German language [9] and included four subscales: "ear signs and symptoms" (items 1-5), "hearing function" (items 6-10), "psychosocial impact" (items [11][12][13][14][15][16][17][18], and the "use of medical resources" (items [19][20][21]. All answers are presented using a 5-point Likert scale.…”
Section: Zcmei-21mentioning
confidence: 99%
See 1 more Smart Citation
“…The ZCMEI-21 has been previously validated in German language [9] and included four subscales: "ear signs and symptoms" (items 1-5), "hearing function" (items 6-10), "psychosocial impact" (items [11][12][13][14][15][16][17][18], and the "use of medical resources" (items [19][20][21]. All answers are presented using a 5-point Likert scale.…”
Section: Zcmei-21mentioning
confidence: 99%
“…Particularly, studies in orthopedics and pain therapy demonstrated that patients with mental health disorders have been associated with less postoperative improvement [17,18]. In patient-reported outcome measures (PROMs), patients with anxiety and depression felt that interventions were less beneficial compared to others without these comorbidities [19][20][21][22]. Given that depressiveness affects the perception of chronical illness [23][24][25], depressive disorders may modulate the relationship between COM symptom burden and the decrease in HRQOL in patients with COM.…”
Section: Introductionmentioning
confidence: 99%
“…The same applies to the predictive value of a positive history childhood trauma for nextvisit sadness and depression. It has been suggested that this correlation is caused by trauma-induced changes to the brain of abused or traumatized children [47,79,80]. In this context, one should consider the fact that about 10% of American youth have experienced at least one episode of sexual assault and 9-19% were subject to physical abuse or a physical assault by the respective caregiver [81].…”
Section: Discussionmentioning
confidence: 99%
“…Next-visit sadness and depression could be predicted in case the patient reported a positive history of childhood trauma, which was the case in 7.9% of study sample. While 89.3% of the patients denied childhood trauma, 2.8% refused to comment on this question [47]. In conclusion, the listed studies' results suggest that surgeons should be aware of the fact that functional recovery following repair of peripheral nerve lesions can be significantly influenced by the prevalence of postoperative stress and pain-catastrophizing.…”
Section: Surgical Repair Of Traumatic Nerve Injuriesmentioning
confidence: 97%
“… 1 Furthermore, chronic pain may interfere with ability to work, sleep, engage in social activities, and ability to pursue leisure or hobbies. 1 Pain has been demonstrated to be specifically predictive of negative changes in QoL and mood, 6 and the reported intensity of a patient’s pain has been shown to be predictive of the level of disability imparted by the nerve injury. 2 , 3 …”
Section: Introductionmentioning
confidence: 99%